A morphometric study of adult human atlas vertebrae in South Gujarat population, India - Patel, Nitixa P.; Gupta, Deepa S. (International Journal of Research in Medical Sciences, 2016)
Background: The atlas (C1) has undergone many structural modification and located at critical point close to the vital centres of the medulla oblongata which can get compressed by a dislocation of the atlanto axial complex or instability of the atlanto axial joint. Knowing of various dimensions of atlas vertebrae are very important for the development of instrumentation related to atlas vertebrae. Methods: In this study, total 100 dried, unbroken atlas vertebrae of unknown age and sex were evaluated in department of anatomy of medical colleges of South Gujarat. All dimensions were measured in bilateral manner using Digital Vernier Callipers with 0.01mm resolution. Results: The mean width of atlas was 71.19 mm. The mean distance between lateral margins of both transverse foramina was 55.48 mm and the inner distance was 44.77 mm. The mean for anteroposterior diameter of vertebral canal of atlas was 28.16mm and transverse diameter was 26.63 mm. The height of anterior arch was 10.21 mm and posterior arch was 8.68mm. The mean for height of facet for dens was 8.96mm and width was 9.18 mm. The mean of anteroposterior diameter of right and left superior articular facet was 20.73 mm and 20.86 mm and transverse diameter was 11.34mm and 11.39mm. The mean of anteroposterior diameter of right and left inferior articular facet was 17.89mm and 17.77mm and transverse diameter was 14.97mm and 15 mm. The mean thickness of vertebral artery groove (VAG) for right and left side was 4.15mm and 3.99mm and width was 8.26 and 8.1 mm. The length of VAG-inner edge (D1) for right and left side was 10.34mm and 10.3mm and length for outer edge (D2) was 14.93mm and 15.1mm. Conclusions: The observations of present study helps in improving understanding of various bony dimensions which could facilitate diagnosis and preoperative planning while operating close to important structures like nerve roots and the vertebral artery and will allow for more accurate modelling of South Gujarat, India.